EVALUASI PENJADWALAN PROYEK DENGAN METODE LINE OF BALANCE (STUDI KASUS : HOTEL SANTIKA BATAM) - Willim Sudarson (Journal of Civil Engineering and Planning (JCEP), 2020)
With the development of technology and information, Indonesia's construction also continues to develop. This can be seen from the many construction projects that are being carried out or that have been completed in Indonesia. In the construction project process, of course it will involve project management so that the construction project goes according to plan and can utilize resources effectively, one of them is by arranging project work scheduling. This study aimed to evaluate project scheduling using the Line of Balance method. The research discussion would include determining the duration of work using the Line of Balance method, comparing the duration of work with existing scheduling and identifying the advantages of project scheduling with the Line of Balance method. The research data util ized scheduling from Santika Hotel Batam construction project. The use of scheduling Line of Balance has advantages in determining the time to start work arranged with each work package. Keywords : evaluation, scheduling, construction projects, Line of Balance